Analisis Pengaruh Kualitas Audit, Pertumbuhan Perusahaan, Opini Audit Tahun Sebelumnya,Profitabilitas, Dan Likuiditas Terhadap Penerimaan Opini Going Concern Pada Perusahaan Manufaktur YangMengalami Financial Distress Di BEI Tahun 2010-2014 - Wigati, Rahmawati Setyo, Dra. Nursiam, M.H., Ak., CA (2016)
This Research aim to analyse the influence of quality of audit, company growth, previous year audit opinion, likuidity and profitability to acceptance of going concern opinion in manufacturing companies have financial distress in BEI year 2010-2014 Population from this research is all manufacture companies listed in Indonesia Stock Exchange ( BEI) 2010-2014. The sampel of the research used purposive sampling and found 12 company, with 5 year of observation. So the total sampel are 56. Data analysis was performed with classical assumption test and logistics regression analysis. The result of research indicate that previous year audit opinion variable have an effect on significant influence to going concern opinion, while variable of quality of audit, company's growth , likuidity and profitability do not have an effect on significant influence to concern going opinion in manufacturing companies have distress financial in BEI year 2010-2014